Factors Affecting the Expression of Recombinant Protein and Improvement Strategies in Chinese Hamster Ovary Cells - Li, Zheng-Mei; Fan, Zhen-Lin; Wang, Xiao-Yin; Wang, Tian-Yun (Frontiers in Bioengineering and Biotechnology, 2022)
Recombinant therapeutic proteins (RTPs) are important parts of biopharmaceuticals. Chinese hamster ovary cells (CHO) have become the main cell hosts for the production of most RTPs approved for marketing because of their high-density suspension growth characteristics, and similar human post-translational modification patterns et al. In recent years, many studies have been performed on CHO cell expression systems, and the yields and quality of recombinant protein expression have been greatly improved. However, the expression levels of some proteins are still low or even difficult-to express in CHO cells. It is urgent further to increase the yields and to express successfully the “difficult-to express ” protein in CHO cells. The process of recombinant protein expression of is a complex, involving multiple steps such as transcription, translation, folding processing and secretion. In addition, the inherent characteristics of molecular will also affect the production of protein. Here, we reviewed the factors affecting the expression of recombinant protein and improvement strategies in CHO cells